Lawrence Dewan y el redescubrimiento de la centralidad de la forma en metafísica (2008)
Lawrence Dewan’s approach of Saint Thomas’s Metaphysics differs from the traditional Thomistic analysis in some relevant aspects. In this paper I intend to show Dewan’s main contribution, which isto have re-discovered the centrality of form in Metaphysics. This Canadian philosopher’s interpretationis important in order to clarify the kinship between form and being and, consequently, to focus on Aquinas’s Metaphysics and Theology correctly.